A Comparative Study of Herbal Memory Enhancers - Agarwal, Nishant; Pareek, Ramesh; Sharma, Vandana; Tripathi, Shailendra; Singh, Ravindra; Kumar, Kartikey (Asian Journal of Pharmaceutical Research and Development, 2023)
Perhaps the most important characteristic that sets humans apart from other animals is memory. Drugs and herbal therapies have been prescribed for centuries to improve people's memories. Ayurveda, the Indian system of medicine, includes a treasure trove of such memory-enhancing medications that are now well-known on a global scale due to their efficacy. Nootropic herbs are herbs that act on the brain, and smart pharmaceuticals are their isolated ingredients. Herbs that improve memory also stimulate the blood flow in the brain. Memory is the most crucial factor in separating one person from another since it helps us identify our unique selves. There are three fundamental types of memory that enable the brain to save, retrieve, and encrypt. Without these fundamental forms of memory, a person also strugglesto develop relationships, learn new things, and perform essential daily tasks. Since recent decades, Indian and Chinese cultures have developed a variety of traditional medicines made from herbs to treat various ailments, including memory loss and decline in cognitive function as well as to boost learning capacity. Nootropic herbs are well-known for their ability to act on the brain and for being smart medications due to their ability to increase blood flow to the brain. This review focuses on organic substances and herbs that improve memory.